Effects of a psycho-educational intervention on direct care workers' communicative behaviors with residents with dementia. Issue 4 (2nd April 2016) - Barbosa, Ana; Marques, Alda; Sousa, Liliana; Nolan, Mike; Figueiredo, Daniela
Abstract: This study assessed the effects of a person-centered care-based psycho-educational intervention on direct care workers' communicative behaviors with people with dementia living in aged-care facilities. An experimental study with a pretest–posttest control-group design was conducted in four aged-care facilities. Two experimental facilities received an 8-week psycho-educational intervention aiming to develop workers' knowledge about dementia, person-centered care competences, and tools for stress management. Control facilities received education only, with no support to deal with stress. In total, 332 morning care sessions, involving 56 direct care workers (female, mean age 44.72 ± 9.02 years), were video-recorded before and 2 weeks after the intervention. The frequency and duration of a list of verbal and nonverbal communicative behaviors were analyzed. Within the experimental group there was a positive change from pre- to posttest on the frequency of all workers' communicative behaviors. Significant treatment effects in favor of the experimental group were obtained for the frequency of inform ( p  < .01, η 2 partial = 0.09) and laugh ( p  < .01, η 2 partial = 0.18). Differences between groups emerged mainly in nonverbal communicative behaviors. The findings suggest that a person-centered care-based psycho-educational intervention can positively affect direct care workers' communicative behaviors with residents with dementia. Further research is required to determine the extent of the benefits of this approach.